Anti-discriminatory Practice in Mental Health Care for Older People. - Tribe, Rachel (Jessica Kingsley Publishers, 2017)
This book provides mental health students and practitioners with the key knowledge to carry out anti-discriminatory practice while working with older people from minority groups. With contributions from experts in the fields of mental health and care for older people, it looks at issues for practice, such as access to services for minority groups.